2018
DOI: 10.1002/qj.3372
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐temporal variability of warm rain events over southern West Africa from geostationary satellite observations for climate monitoring and model evaluation

Abstract: This article presents the spatio‐temporal variability of warm rain events over southern West Africa (SWA) during the summer monsoon season for the first time, using Spinning Enhanced Visible Infrared Radiometer (SEVIRI) observations on the Meteosat geostationary satellites. The delineation of warm rain events is based on the principle that precipitating low‐level clouds are associated with either sufficient water content or large cloud droplet size. Capitalising on the ability of space‐borne radar to resolve v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 93 publications
1
7
0
Order By: Relevance
“…During the latter, the main rainband has moved into the Sahel, creating somewhat drier conditions in the DACCIWA region (4.9 versus 5.5 mm·danormaly1 in IMERG; not shown). The often light (and sometimes warm) rains during this period (Young et al ., ) appear to be particularly difficult to capture for IMERG (M. Maranan, personal communication, 2019). In contrast, the dry bias on forecast day 1 in the models tends to get smaller from period 1 to period 2.…”
Section: Resultsmentioning
confidence: 99%
“…During the latter, the main rainband has moved into the Sahel, creating somewhat drier conditions in the DACCIWA region (4.9 versus 5.5 mm·danormaly1 in IMERG; not shown). The often light (and sometimes warm) rains during this period (Young et al ., ) appear to be particularly difficult to capture for IMERG (M. Maranan, personal communication, 2019). In contrast, the dry bias on forecast day 1 in the models tends to get smaller from period 1 to period 2.…”
Section: Resultsmentioning
confidence: 99%
“…Huffman and Norman, ), further analysis of the rainfall types is required with a refined definition of potential warm‐rain areas. Possible options include a method introduced in Young et al () where a combination of cloud optical depth and effective radius information from SEVIRI was used to delineate these areas.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The latter may explain the enhanced pre‐noon rainfall probability that was found at the Benin coast based on rain‐gauge recordings (Fink et al ). Similarly, using continuous geostationary‐based cloud property retrievals from SEVIRI, Young et al () found the highest frequency of warm rain along the coastline around midday. At the Coast, the frequency of WCCs already peaks in the early afternoon, which is partly caused by coastal convection forming a contiguous line with strong radar echoes (not shown).…”
Section: Spatio‐temporal Climatologies Of Rainfall Typesmentioning
confidence: 92%
“…Over land, TRMM generally underestimates the frequency and amount of rain from warm clouds, typically found over coastal areas with onshore trade or monsoonal winds and in the vicinity of mountains (e.g., Dinku et al 2018). Another potential problem is an underestimation of extreme values, partly due to beam filling in the microwave bands (Young et al 2014;Monsieurs et al 2018). Over ocean, precipitation detection is more challenging than over land and calibration with gauges is not possible.…”
Section: B Observationsmentioning
confidence: 99%
“…4c in Berg et al 2010) and a comparatively large dry bias (Huffman et al 2007) in these regions. The often light rain from warm clouds is generally challenging to detect from space (Young et al 2018). This suggests that the calibration (and skill) of the model is presumably assessed worse in these regions than it actually is-particularly in recent years, as ECMWF has addressed relevant problems in their forecast model (Ahlgrimm and Forbes 2014).…”
Section: A Calibration and Reliability Of The Ecmwf Ensemblementioning
confidence: 99%